Tariquidar Is an Inhibitor and Not a Substrate of Human and Mouse P-glycoprotein - Weidner, Lora D. (Drug Metab Dispos, 2016)
Since its development, tariquidar (TQR; XR9576; N-[2-[[4-[2-(6,7-Dimethoxy-3,4-dihydro-1H-isoquinolin-2-yl)ethyl]phenyl]carbamoyl]-4,5-dimethoxyphenyl]quinoline-3-carboxamide) has been widely regarded as one of the more potent inhibitors of P-glycoprotein (P-gp), an efflux transporter of the ATP-binding cassette (ABC) transporter family. A third-generation inhibitor, TQR exhibits high affinity for P-gp, although it is also a substrate of another ABC transporter, breast cancer resistance protein (BCRP). Recently, several studies have questioned the mechanism by which TQR interfaces with P-gp, suggesting that TQR is a substrate for P-gp instead of a noncompetitive inhibitor. We investigated TQR and its interaction with human and mouse P-gp to determine if TQR is a substrate of P-gp in vitro. To address these questions, we used multiple in vitro transporter assays, including cytotoxicity, flow cytometry, accumulation, ATPase, and transwell assays. A newly generated BCRP cell line was used as a positive control that demonstrates TQR-mediated transport. Based on our results, we conclude that TQR is a potent inhibitor of both human and mouse P-gp and shows no signs of being a substrate at the concentrations tested. These in vitro data further support our position that the in vivo uptake of [(11)C]TQR into the brain can be explained by its high-affinity binding to P-gp and by it being a substrate of BCRP, followed by amplification of the brain signal by ionic trapping in acidic lysosomes.